MicroRNA-21 as a Regulator of Cancer Stem Cell Properties in Oral Cancer - Milica Jaksic Karisik; Milos Lazarevic; Dijana Mitic; Maja Milosevic Markovic; Nicole Riberti; Drago Jelovac; Jelena Milasin (Cells)
Oral squamous cell carcinoma (OSCC) is a highly aggressive malignancy with poor prognosis, mainly due to the presence of cancer stem cells (CSCs), a small subpopulation of cells that contribute to therapy resistance and tumor progression. The principal objective of this study was to investigate the role of miRNA-21 in the maintenance of cancer cell stemness and the possibility of altering it. The CD44 antigen was used as a marker for CSC isolation from oral cancer cell cultures. CD44+ and CD44− populations were sorted via magnetic separation. miRNA-21 inhibition was performed in CD44+ cells via transfection. CD44+ cells possessed a significantly higher migration and invasion potential compared to CD44− cells, higher levels of miRNA-21 (p = 0.004) and β-catenin (p = 0.005), and lower levels of BAX (p = 0.015). miRNA-21 inhibition in CD44+ cells reduced migration, invasion, and colony formation while increasing apoptosis. Stemness markers were significantly downregulated following miRNA-21 inhibition: OCT4 (p = 0.013), SOX2 (p = 0.008), and NANOG (p = 0.0001), as well as β-catenin gene (CTNNB1) (p < 0.05), an important member of WNT signaling pathway. Apoptotic activity was enhanced, with a significant downregulation of the antiapoptotic Bcl-2 (p = 0.008) gene. In conclusion, miRNA-21 plays a critical role in the regulation of oral cancer CD44+ cells properties. Targeting and inhibiting miRNA-21 in CD44+ cells could represent a promising novel strategy in OSCC treatment.